Measures to support informal care for the older adults in Kazakhstan: a review of the current status - Zhylkybekova, Aliya; Turlayev, Andrey; Grjibovski, Andrej M.; Koshmaganbetova, Gulbakit K. (Frontiers in Public Health, 2023)
The demand for informal caregivers to support the elderly has grown worldwide in recent decades. However, informal caregivers themselves require support. This article aims to examine existing support measures for caregivers of the elderly in the Republic of Kazakhstan. Relevant articles and grey literature were identified through manual searches on Google and Google Scholar, as well as electronic searches using indexed databases like PubMed, Web of Science, and Scopus. Moreover, the reference lists of identified sources and government ministry websites were meticulously scrutinized. This review highlights the scarcity of research on caregiver support measures in Kazakhstan, supported by the lack of peer-reviewed articles on this subject. A comprehensive analysis of the literature shows that in Kazakhstan's legislative framework, 'caregivers' exclusively refers to individuals providing care for a first-degree disability. The responsibility of caring for elderly parents lies with able-bodied children. However, there is a lack of registration and assessment procedures to evaluate the burden and quality of life of caregivers. As a result, the medical and social support provided to caregivers is standardized, failing to adequately address their unique needs and requirements. The analysis of current support measures for informal caregivers highlights the need to develop support mechanisms and recognize individuals providing informal care as key figures in the long-term care system.